Peran Komunikasi Organisasi dalam Meningkatkan Kinerja Organisasi - Sri Yulianti Mozin; Alfiyah Agussalim; Nur Rizka Ahen; Marvinesya Tobuto; Sarlin Idris; Siti Maudhy Nisrina Kilo; Dwi Hazriati Musdhalifah; Arya Anugerah Pakaya (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the role of organizational communication in improving organizational performance using a systematic literature review approach with a descriptive qualitative method. The data were obtained from various relevant scientific literature sources, including national journals and academic articles discussing organizational communication and performance. The results indicate that organizational communication plays a significant role in enhancing performance through effective vertical and horizontal communication patterns, clarity of information flow, and improved work coordination. In addition, organizational communication contributes to building harmonious working relationships, increasing motivation, and strengthening organizational commitment. Leadership plays a crucial role in managing communication effectiveness within the organization. However, communication effectiveness is also influenced by supporting and inhibiting factors, such as work environment, communication skills, and differences in individual perceptions. Therefore, organizations need to manage communication strategically to achieve optimal performance. This study provides theoretical contributions to the development of organizational communication studies and practical implications for organizations in improving communication effectiveness.